Surface Plasmon Plastic Optical Fiber Resonance with Multi-Layer as Chemical Sensor - Khatar, Emad; Bassam, Sudad Salman (Iraqi Journal of Physics, 2021)
A chemical optical fiber sensor based on surface plasmon resonance (SPR) was developed and implemented using multimode plastic optical fiber. The sensor is used to detect and measure the refractive index and concentration of various chemical materials (Urea, Ammonia, Formaldehyde and Sulfuric acid) as well as to evaluate the performance parameters such as sensitivity, signal to noise ratio, resolution and figure of merit. It was noticed that the value of the sensitivity of the optical fiber-based SPR sensor, with 60nm and 10 mm long, Aluminum(Al) and Gold (Au) metals film exposed sensing region, was 4.4 μm, while the SNR was 0.20, figure of merit was 20 and resolution 0.00045. In this work a multimode plastic optical fiber with a core diameter of 980 μm, fluorinated polymer cladding of 20 μm and a numerical aperture of 0.51 was used.